Perancangan User Interface Pada Website Promosi Ekonomi Kreatif Menggunakan Metode Design Thinking Di Banyuwangi - Rahayu, Titis Esti; Haq, Endi Sailul; Umam, Khoirul (Sekolah Tinggi Ilmu Komputer PGRI Banyuwangi, 2025)
Creative economy is a sustainable economic development concept based on creativity, encompassing arts, culture, science, technology, engineering, and telecommunications. In Banyuwangi, the creative economy is facilitated by the Banyuwangi Youth Creative Festival (BYCN), supported by the Department of Culture and Tourism. However, many creative economy players in Banyuwangi still lack promotional design plans, including websites. This study aims to design a user interface for a creative economy promotion website using the design thinking method, which includes five stages: Empathy, Definition, Ideation, Prototype, and Testing. This method focuses on consumer-centered innovation, emphasizing product and service design that attracts attention in the business world. Testing uses the usability scale with web maze to evaluate the prototype created with the user interface developed by 30 respondents. The results of the testing using the System Usability Scale (SUS) showed a score of 79.5, which falls into the ACCEPTABLE category. Adjective ratings assessment indicated an EXCELLENT result and a grade scale of B. With these results, this study demonstrates that the designed website meets usability standards and user feedback indicates that the user interface (UI) is easy to use.